Overexpression of Rice Wall-Associated Kinase 25 (OsWAK25) Alters Resistance to Bacterial and Fungal Pathogens - Harkenrider, Mitch; Sharma, Rita; De Vleesschauwer, David; Tsao, Li; Zhang, Xuting; Chern, Mawsheng; Canlas, Patrick; Zuo, Shimin; Ronald, Pamela C. (PloS one, 2016)
Wall-associated kinases comprise a sub-family of receptor-like kinases that function in plant growth and stress responses. Previous studies have shown that the rice wall-associated kinase, OsWAK25, interacts with a diverse set of proteins associated with both biotic and abiotic stress responses. Here, we show that wounding and BTH treatments induce OsWAK25 transcript expression in rice. We generated OsWAK25 overexpression lines and show that these lines exhibit a lesion mimic phenotype and enhanced expression of rice NH1 (NPR1 homolog 1), OsPAL2, PBZ1 and PR10. Furthermore, these lines show resistance to the hemibiotrophic pathogens, Xanthomonas oryzae pv. oryzae (Xoo) and Magnaporthe oryzae, yet display increased susceptibility to necrotrophic fungal pathogens, Rhizoctonia solani and Cochliobolus miyabeanus.